Increase Sales with Influencers and Word of Mouth: a Live Streaming Study on Cosmetics and Fashion Products at Shopee Batam Customers - Mulyaningtyas, Dian; Yanti, Vera (Pusat P2M Politeknik Negeri Batam, 2025)
This study tries to determine the impact of influencers and word of mouth on purchasing decisions with live streaming as a moderating variable on cosmetic and fashion products. This study uses the population of Batam City People who have used the Shopee application. This quantitative research uses the path analysis method as the data analysis technique. Data collection will be done by distributing questionnaires to the Batam City community. Using the Lemeshow formula, 150 respondents were obtained in Batam City. The research findings show that influencers have a positive and significant effect on purchasing decisions on cosmetic and fashion products, word of mouth has a positive and significant impact on buying decisions on cosmetic and fashion products, live streaming as a moderating variable weakens the influence of influencers on purchasing decisions on cosmetic and fashion products, and live streaming as a moderating variable strengthens the impact of word of mouth on buying decisions on cosmetic and fashion products